2005
DOI: 10.1152/ajpcell.00019.2005
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive secretion of serum albumin requires reversible protein tyrosine phosphorylation events in trans-Golgi

Abstract: Serum albumin secretion from rat hepatocytes proceeds via the constitutive pathway. Although much is known about the role of protein tyrosine phosphorylation in regulated secretion, nothing is known about its function in the constitutive process. Here we show that albumin secretion is inhibited by the tyrosine kinase inhibitor genistein but relatively insensitive to subtype-selective inhibitors or treatments. Secretion is also blocked in a physiologically identical manner by the tyrosine phosphatase inhibitors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…Thus apoE secretion can be considered a prototype for the understanding of the secretion of other macrophage proteins. Recent studies have demonstrated that constitutive secretion is regulated, 40,41 involving kinases, phosphatases, receptors, and, typically, the microtubule network. 42 Microtubules mediate long-range transport in vesicle traffic via kinesin and dynein motor proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Thus apoE secretion can be considered a prototype for the understanding of the secretion of other macrophage proteins. Recent studies have demonstrated that constitutive secretion is regulated, 40,41 involving kinases, phosphatases, receptors, and, typically, the microtubule network. 42 Microtubules mediate long-range transport in vesicle traffic via kinesin and dynein motor proteins.…”
Section: Discussionmentioning
confidence: 99%
“…76,83,84 In view of previous studies indicating that apoE secretion could be stimulated by apoA-I and by HDL, 17,19,38,47 we hypothesized that even basal apoE secretion must be under some form of regulation. We showed that disruption of microtubules inhibited basal apoE secretion, whereas disruption of the actin skeleton had no effect.…”
Section: Macrophage Apoe Secretion Involves Protein Kinase a Intracementioning
confidence: 95%
“…However, it is noteworthy that use of the terms constitutive and constitutive-like for these pathways does not mean that these routes are not subject to control. Indeed, it is clear that the flow of secretory molecules through the constitutive pathway can be modulated by tyrosine phosphorylation of Golgi proteins (Webb et al, 2005) and retrieval of specific membrane proteins from maturing secretory granules is modulated by phosphorylationdependent recruitment of adaptor proteins (Eaton et al, 2000;Hinners et al, 2003;Kakhlon et al, 2006).…”
Section: Introductionmentioning
confidence: 99%